Introduction of H2C2‐type zinc‐binding residues into HIV‐2 Vpr increases its expression level. Issue 1 (19th December 2017) - Koga, Ryoko; Yamamoto, Minami; Ciftci, Halil Ibrahim; Otsuka, Masami; Fujita, Mikako
Abstract : Human immunodeficiency virus type 2 has two structurally similar proteins, Vpx and Vpr. Vpx degrades the host anti‐viral protein SAMHD1 and is expressed at high levels, while Vpr is responsible for cell cycle arrest and is expressed at much lower levels. We constructed a Vpr mutant with a high level of expression by replacing the amino acids HHCR/HHCH with a putative H2C2‐type zinc‐binding site that is carried by Vpx. Our finding suggests that during the evolution of Vpr and Vpx, zinc‐binding likely became a mechanism for regulating their expression levels. Abstract : HIV‐2 has two structurally similar proteins, Vpx and Vpr, which vary in both function and expression. We show here that replacing the HHCH or HHCR motif in Vpr with the C2H2‐type zinc‐binding motif normally found in Vpx increases the expression level of Vpr. This suggests that zinc binding likely regulates the expression levels of Vpr and Vpx during the evolution of HIVs and SIVs.